Comparison of hospital episode statistics and central cardiac audit database in public reporting of congenital heart surgery mortality - Westaby, Stephen; Archer, Nicholas; Manning, Nicola; Adwani, Satish; Grebenik, Catherine; Ormerod, Oliver; Pillai, Ravi; Wilson, Neil (BMJ, 2007)
Objective To verify or refute the value of hospital episode statistics (HES) in determining 30 day mortality after open congenital cardiac surgery in infants nationally in comparison with central cardiac audit database (CCAD) information.Design External review of paediatric cardiac surgical outcomes in England (HES) and all UK units (CCAD), as derived from each database.Setting Congenital heart surgery centres in the United Kingdom.Data sources HES for congenital heart surgery and corresponding information from CCAD for the period 1 April 2000 to 31 March 2002. HES was restricted to the 11 English centres; CCAD covered all 13 UK centres.Main outcome measure Mortality within 30 days of open heart surgery in infants aged under 12 months.Results In a direct comparison for the years when data from the 11 English centres were available from both databases, HES omitted between 5% and 38% of infants operated on in each centre. A median 40% (range 0-73%) shortfall occurred in identification of deaths by HES. As a result, mean 30 day mortality was underestimated at 4% by HES as compared with 8% for CCAD. In CCAD, between 1% and 23% of outcomes were missing in nine of 11 English centres used in the comparison (predominantly those for overseas patients). Accordingly, CCAD mortality could also be underestimated. Oxford provided the most complete dataset to HES, including all deaths recorded by CCAD. From three years of CCAD, Oxford's infant mortality from open cardiac surgery (10%) was not statistically different from the mean for all 13 UK centres (8%), in marked contrast to the conclusions drawn from HES for two of those years.Conclusions Hospital episode statistics are unsatisfactory for the assessment of activity and outcomes in congenital heart surgery. The central cardiac audit database is more accurate and complete, but further work is needed to achieve fully comprehensive risk stratified mortality data. Given unresolved limitations in data quality, commercial organisations should reconsider placing centre specific or surgeon specific mortality data in the public domain.